Treatment of ursodeoxycholic acid with glucocorticoids and immunosuppressants may improve the long-term survival rate in primary biliary cholangitis patients. Issue 46 (18th November 2022) - Wang, Zi-Long; Jin, Rui; Hao, Mei; Xie, Yan-Di; Liu, Zhi-Cheng; Wang, Xiao-Xiao; Feng, Bo
Abstract : Primary biliary cholangitis (PBC) is an autoimmune cholestatic liver disease. The clinical effectiveness of ursodeoxycholic acid (UDCA) plus glucocorticoids and/or immunosuppressants remains controversial in PBC patients. The study aimed to compare the efficacy of monotherapy and combination therapy in patients with PBC and to assess the factors affecting the efficacy. In this retrospective study, 266 patients diagnosed with PBC were divided into monotherapy group (UDCA), double therapy group (UDCA plus glucocorticoids or immunosuppressants), and triple therapy group (UDCA plus glucocorticoids and immunosuppressants) according to different treatments. Demographic characteristics, immune parameters, biochemistry profiles, and other indicators were evaluated at baseline, 6 months, and 1 year following treatment. The prognosis was evaluated using the Paris II standard. The liver transplant-free survival at 3, 5, 10, and 15 years was predicted by GLOBE score. All statistical analyses were conducted using SPSS (version 24) software (SPSS Inc, Chicago, IL). The long-term survival rate of the triple therapy group was significantly improved compared with the monotherapy group ( P = .005). In addition, multivariate analysis showed that abnormal platelet count, alkaline phosphatase, and albumin levels were risk factors for poor response. When IgG levels were elevated but below twice the upper limit of normal, the clinical benefit was not significant compared with monotherapy ( P > .05). Compared with monotherapy and double therapy, triple therapy may improve the long-term survival rate of PBC patients. Abnormal platelet count, alkaline phosphatase, and albumin levels were associated with a poor prognosis.